2020
DOI: 10.14309/ctg.0000000000000203
|View full text |Cite
|
Sign up to set email alerts
|

Hepatitis C Virus Clearance by Direct-Acting Antivirals Agents Improves Endothelial Dysfunction and Subclinical Atherosclerosis: HEPCAR Study

Abstract: INTRODUCTION: Hepatitis C virus (HCV) infection has been related to increased cardiovascular (CV) risk. The aim of this study was to analyze the impact of sustained virological response (SVR) on endothelial dysfunction and subclinical atherosclerosis in patients with hepatitis C virus treated with direct-acting antiviral agents. METHODS: A total of 114 patients were prospectively recruited and underwent CV risk assessment including (i) endothelial dysfunction determined… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
18
0
4

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(24 citation statements)
references
References 49 publications
(52 reference statements)
2
18
0
4
Order By: Relevance
“…Our results were in line with the recent multicenter and prospective study (HEPCAR Study) of HCV patients treated by DAAs with long follow-up period which demonstrated significant reduction in levels endothelial dysfunction markers VCAM-1 and e-selectin at SVR point in all participants and continued in reduction during follow-up for one year ( Muñoz-Hernández et al 2020 ).…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…Our results were in line with the recent multicenter and prospective study (HEPCAR Study) of HCV patients treated by DAAs with long follow-up period which demonstrated significant reduction in levels endothelial dysfunction markers VCAM-1 and e-selectin at SVR point in all participants and continued in reduction during follow-up for one year ( Muñoz-Hernández et al 2020 ).…”
Section: Discussionsupporting
confidence: 91%
“…The same was reported by Muñoz-Hernandez et al . ( Muñoz-Hernández et al 2020 ) where a continuous improvement in vascular function markers at SVR time and 1 year after treatment was observed. Therefore, the effect is unlikely to be associated with the pleiotropic effect of DAA.…”
Section: Discussionmentioning
confidence: 85%
See 1 more Smart Citation
“…The obtained results show that hepatitis C group had significantly higher concentrations of ICAM-1 and sVCAM-1 compared to controls which is in accordance with most results of previous studies dealing with HCV, endothelial dysfunction and higher risk of CVD ( Stanimirovic et al, 1997 ; Blann et al, 1999 ; Martinic-Popovic et al, 2014 ). Authors of some recent studies went a step further alleging that the new DAA treatment reverses these chronic HCV effects and enhances endothelial function ( Schmidt et al, 2018 ; Davis et al, 2018 ; Muñoz Hernández et al, 2020 ). In our research, HCV patients had decreased VEGF-A compared to healthy controls opposing several earlier studies connecting higher levels of VEGF-A with the risk of ischemic CVD ( Shoamanesh et al, 2016 ).…”
Section: Discussionmentioning
confidence: 99%
“…Only a few studies about MPs in patients with hepatitis C undergoing DAA therapy have been performed 33,34 . The aims of the following study were: first, compare MPs level between patients with CHC and control group of healthy volunteers; second, evaluate changes of MPs levels during DAA therapy; third, analyzed MPs changes in subpopulations according to gender, genotypes, and fibrosis stage.…”
Section: Chronic Hepatitis Cmentioning
confidence: 99%